Reducing distress and promoting resilience: a preliminary trial of a CBT skills intervention among recently HIV-diagnosed MSM in China. (23rd August 2018) - Yang, Joyce P.; Simoni, Jane M.; Dorsey, Shannon; Lin, Zhang; Sun, Meiyan; Bao, Meijuan; Lu, Hongzhou
ABSTRACT: People living with HIV/AIDS (PLWHA) in China experience significant psychological distress, due to high rates of stigma and low availability of mental health resources. Recently diagnosed Chinese PLWHA who are men who have sex with men (MSM) are particularly vulnerable to distress, facing both HIV and sexual orientation stigma. Reducing distress and enhancing psychological resilience is critical in promoting wellbeing. However, no research to date has examined evidence-based interventions to reduce psychological symptoms and improve resilience in this population. Based on qualitative research on their mental health needs, we developed a culturally tailored, brief 3-session CBT skills-based intervention for integration into primary care [Yang, J. P., Simoni, J., Cheryan, S., Shiu, C., Chen, W., Zhao, H., & Lu, H. (2018). The development of a brief distress reduction intervention for individuals recently diagnosed with HIV in China. Cognitive Behavioral Practice, 25 (2), 319–334. doi:10.1016/j.cbpra.2017.08.002 ]. The intervention includes cognitive restructuring to address depressive thought patterns, behavioral activation to decrease isolation, and paced breathing to reduce anxiety. We conducted a pilot Type 1 hybrid effectiveness-implementation trial assessing pre–post mental health outcomes as well as feasibility, acceptability, and appropriateness information. Ten recently diagnosed MSM completed the research protocol of three individual weekly sessions. Paired-samples t tests demonstrated significant reduction in HIV-related distress, depression, problems with adjustment, as well as improvements in resilience, and perceived social support. Participants and community advisory board members found the intervention highly acceptable, appropriate, and feasible. Preliminary data from the first known study examining a psychological intervention with evidence-based components for recently diagnosed Chinese MSM suggests that this brief intervention may be useful for reducing distress and promoting resilience.